ON THE TEACHING OF AUDITING. - Chamberlain, Henry T. (The Accounting Review, 1935)
Abstract The statement that a teacher is satisfied with the results obtained in his course should be regarded as news, comparable, perhaps, to the statement that a man bites a dog, according to the author of this article. What he has to say, therefore, is not news, for he is thoroughly dissatisfied with the results obtained in the courses in auditing in his university. This should not come as a shock to teachers of accounting, for the author thinks, educators will all agree that the course in auditing is the most unsatisfactory course in the accounting curriculum from the teacher's viewpoint as well as from the student's. What the author has to say on this subject is not intended as a criticism of auditing textbooks. A textbook has limits, and within those limits the authors of the standard books have done an excellent job of presenting the fundamental principles of auditing and the methods of preparing audit working papers and reports. However, a need exists for something to supplement the textbook if teachers are to give the student a real grasp of the subject.